2012
DOI: 10.3201/eid1802.111293
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Human Bocavirus 1 Infection with Respiratory Disease in Childhood Follow-up Study, Finland

Abstract: Since its discovery in 2005, human bocavirus type 1 has often been found in the upper airways of young children with respiratory disease. But is this virus the cause of the respiratory disease or just an innocent bystander? A unique study in Finland, which examined follow-up blood samples of 109 healthy children with no underlying illness starting at birth and until they were 13 years of age, found that acute bocavirus infection resulted in respiratory disease. All children had been infected by age 6. Most ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
111
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(123 citation statements)
references
References 35 publications
6
111
0
4
Order By: Relevance
“…The incidence of serologically verified acute HBoV1 infections has been shown to be highest during the second year of life, and short-term viremia has also been found to be an excellent marker of an acute HBoV1 infection. 21,27,28,64 Studies of nasopharyngeal samples have shown persistence of HBoV1 DNA for several months. [65][66][67][68] HBoV1 seroprevalence ranges from 25% in infants younger than 1 year to 93% and 100% in children of 3 (ref.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of serologically verified acute HBoV1 infections has been shown to be highest during the second year of life, and short-term viremia has also been found to be an excellent marker of an acute HBoV1 infection. 21,27,28,64 Studies of nasopharyngeal samples have shown persistence of HBoV1 DNA for several months. [65][66][67][68] HBoV1 seroprevalence ranges from 25% in infants younger than 1 year to 93% and 100% in children of 3 (ref.…”
Section: Discussionmentioning
confidence: 99%
“…The causative role of HBoV1 in clinical manifestations other than respiratory diseases remains to be assessed. 64 Accurate diagnosis requires antibody analysis or PCR of serum; PCR of nasopharyngeal samples alone is insufficient. 27 In our study all serum samples investigated were HBoV1 PCR negative.…”
Section: Discussionmentioning
confidence: 99%
“…However, a strong correlation between the respiratory disease and the viral load (>10 4 DNA copies) has been shown, together with the detection of the virus with the highest prevalence (and in single infection) in asymptomatic subjects. 11,12 Considering the causative association of HBoV with respiratory diseases, Meriluoto, et al, 13 followed up 109 newborn infants up to their adolescence and noticed an association between the primary infection (documented by serum viral load, IgM and IgG seroconversion) and respiratory disease (high and low), which predominantly occurred in children younger than 2 years old. Conversely, in cases of re-infection no respiratory symptoms were associated.…”
Section: Discussionmentioning
confidence: 99%
“…На відміну від дорослих в етіологіч-ному спектрі ГРЗ у дитячому віці істотно частіше спо-стерігаються бокавіруси та Moraxella catarrhalis, а також коінфікування різними вірусами [8].…”
unclassified